Anatomical Evidence for Parasympathetic Innervation of the Renal Vasculature and Pelvis. Issue 12 (December 2022) - Cheng, Xiaofeng; Zhang, Yongsheng; Chen, Ruixi; Qian, Shenghui; Lv, Haijun; Liu, Xiuli; Zeng, Shaoqun
Significance Statement: The kidneys critically contribute to body homeostasis under the control of the autonomic nervous system. Although the cholinergic effects on renal function have been widely confirmed, there is still lack of evidence for the cholinergic innervation of the kidney. Using a genetically modified mouse model and immunostaining, the authors found evidence suggesting that cholinergic nerves supply the main renal artery, segmental renal artery, and renal pelvis. They also found expression of acetylcholine receptors in the renal artery and its segmental branches. This anatomical evidence for parasympathetic innervation of the kidney may suggest new avenues for investigation into interventional strategies for refractory hypertension, renal innervation mechanisms, and other neuroendocrine diseases associated with renal dysfunction. Visual Abstract: Abstract : Background: The kidneys critically contribute to body homeostasis under the control of the autonomic nerves, which enter the kidney along the renal vasculature. Although the renal sympathetic and sensory nerves have long been confirmed, no significant anatomic evidence exists for renal parasympathetic innervation. Methods: We identified cholinergic nerve varicosities associated with the renal vasculature and pelvis using various anatomic research methods, including a genetically modified mouse model and immunostaining. Single-cell RNA sequencing (scRNA-Seq) was used to analyze the expression of AChRs in the renal artery and its segmental branches. To assess the origins of parasympathetic projecting nerves of the kidney, we performed retrograde tracing using recombinant adeno-associated virus (AAV) and pseudorabies virus (PRV), followed by imaging of whole brains, spinal cords, and ganglia. Results: We found that cholinergic axons supply the main renal artery, segmental renal artery, and renal pelvis. On the renal artery, the newly discovered cholinergic nerve fibers are separated not only from the sympathetic nerves but also from the sensory nerves. We also found cholinergic ganglion cells within the renal nerve plexus. Moreover, the scRNA-Seq analysis suggested that acetylcholine receptors (AChRs) are expressed in the renal artery and its segmental branches. In addition, retrograde tracing suggested vagus afferents conduct the renal sensory pathway to the nucleus of the solitary tract (NTS), and vagus efferents project to the kidney. Conclusions: Cholinergic nerves supply renal vasculature and renal pelvis, and a vagal brain-kidney axis is involved in renal innervation.